Blunt Cerebrovascular Injury (BCVI): Rare Entity with Dangerous Implications - Affirul, CA; Yuzaidi, M; Tiong, VE; Rizal, IA (Gazi Univ, Fac Med, 2024)
Blunt cerebrovascular incidents (BCVI) is an uncommon occurrence amounting only up to 1% in most trauma registries. Even with a screening protocol, the documented incidence is just up to 2.7%. Despite a rare occurrence, the risk of complication related to BCVI can be devastating especially stroke. An untreated BCVI leads to 10-40% risk of developing stroke which can be fatal. The overall mortality was 59%, and 80% of that death is attributed to BCVI. We report a case who presented with traumatic neck injury subsequently diagnosed with BCVI. The presentation, diagnosis and therapy are discussed.